Successful conservative treatment of cesarean scar ectopic pregnancy with local injections of absolute ethanol - Toshiyuki Kakinuma; Kaoru Kakinuma; Yoshio Matsuda; Kaoru Yanagida; Hirotsune Kaijima; Michitaka Ohwada (Wolters Kluwer Medknow Publications, 2021)
Cesarean scar ectopic pregnancy (CSEP) is becoming more common worldwide. Here, we report a case of cesarean scar pregnancy successfully treated using transvaginal ethanol injection. A 31-year-old female (gravida 3, para 2) with two prior cesarean sections presented at 9 weeks and 3 days of pregnancy. Her serum human chorionic gonadotropin level was 91,798 mIU/mL. CSEP was confirmed by transvaginal ultrasonography, pelvic magnetic resonance imaging, and color Doppler ultrasonography. Transvaginal absolute ethanol local injection under transvaginal ultrasound guidance was performed. She was discharged 7 days after treatment with no complications and resumed normal menses 1 month after treatment. We describe a safe and successful treatment option for CSEP.